VD_FINDINFO HC / 2015 / 169 vom 19. Februar 2015 - VD Tribunal cantonal (2015)
TRANSACTION JUDICIAIRE, MESURE PROVISIONNELLE, RADIATION DU RÔLE, ASSISTANCE JUDICIAIRE | 105 al. 1 CPC (CH), 109 al. 1 CPC (CH), 241 al. 1 CPC (CH), 241 al. 2 CPC (CH)